Preparation and In-vitro Evaluation of Sublingual Tablets of Captopril - نسرين قدار; غيث الشيخ موسى (Latakia University Journal -Medical Sciences Series, 2022)
Captopril is an angiotensin converting enzyme inhibitor. It is used by sublingual route to treat hypertension crises. The sublingual route achieves a rapid onset of action compared to the oral route due to the rapid and direct absorption of the drug into the blood circulation. This study aims to prepare captopril sublingual tablets by using crosspovidone and crosscarmellose sodium as superdisintegrants. The tablets were prepared by direct compression method and several physicochemical tests were performed. All formulations showed physicochemical specifications in compliance with constitutional requirements. The results of the disintegration time and of the in vitro dissolution studies showed that the F1 formula that contains 4% crosspovidone has the lowest disintegration time of 25 seconds and releases more than 90% of the drug substance within less than 6 minutes. The results also showed the importance of the presence of mannitol in the formula.